Pembaharuan Hukum Acara Pidana Tentang Persidangan Online Dalam Keadaan Darurat - Mega Ayu Werdiningsih (Widya Yuridika, 2022)
In 2018 the Supreme Court launched an electronic court service system (E-Court) and a year later an online court system or E-Litigation was formed which is part of the E-Court. This E-Litigation system was only implemented for criminal trials when Indonesia entered a Health Emergency status due to the spread of the COVID-19 virus which created large-scale social restrictions (PSBB) in 2020, through Supreme Court Regulation (Perma) Num.. 4 of 2020 concerning Administration and Trial of Criminal Cases in Courts Electronically. With the form of juridical-normative research method, this research looks for data by studying literature in the form of legislation and related literature. The results of this study indicate that Perma No. 4 of 2020 which has imposed E-Litigation on criminal cases as a whole has substance that is not only related to administrative matters (registrars) of criminal case trials but has also influenced basic norms in criminal procedural law as regulated in the Criminal Procedure Code